Correlation of Epithelial Cell Abnormality in Cervical Cytology with Cervical Histology - Shrestha, Richa; Sinha, Kavita; Sharma, Nirmala; Shrestha, Anil (Journal of Nepalgunj Medical College, 2020)
Introduction: Cervical cancer is the second most common cancer in females worldwide and third most common cancer in Nepal. Conventional Pap smear is the most widely used screening tool for detecting premalignant and malignant lesions of cervix. Cytohistological correlation of Pap smear is a widely accepted method for analysis of various factors leading to discrepancies in diagnosis and internal quality assurance. Aims: To study the cytohistological correlation of epithelial cell abnormality in Pap smear in Nepalgunj Medical College Teaching Hospital, Kohalpur, Banke, Nepal. Methods: This is a hospital based prospective cross sectional study carried out at Department of Pathology, NGMC, Kohalpur, Nepal from August 2018 to January 2020. The study included 137 cases of Pap smear with epithelial cell abnormality and correlated with corresponding histopathological findings. Results: The age of patients ranged from 20-80 years with the number of cases seen in the range of 30-39 years (n=44; 32.1%). Whitish discharge per vaginum was most common presenting symptom. High grade squamous intraepithelial lesion (HSIL) was the most common abnormal finding in Pap smear with a frequency of 40 (29.1%) cases. Out of 137 cases of Pap smear 57 (41.6%) cases showed discrepancies in cervical biopsy. All cases of Squamous Cell Carcinoma (SCC) were correctly diagnosed by Pap smear. The overall sensitivity of smear test was 84%. After evaluating cytohistological correlation, the Positive Predictive Value (PPV) was found to be 100% for SCC, 52% for HSIL and 59% for Low grade squamous intraepithelial lesion (LSIL). Conclusion: The current study revealed a good correlation between cervical cytology and biopsy in Pap smear showing epithelial cell abnormalities. Thus, cytology and histology are complementary to each other and helps to reduce discrepancies.